Impact of blinding interviewers to written applications on ranking of Gynecologic Oncology fellowship applicants from groups underrepresented in medicine - Jennifer Haag; Brooke E. Sanders; Joseph Walker Keach; Carolyn Lefkowits; Jeanelle Sheeder; Kian Behbakht (Elsevier, 2022)
Biases in application review may limit access of applicants who are underrepresented in medicine (URM) to graduate medical training opportunities. We aimed to evaluate the association between blinding interviewers to written applications and final ranking of all applicants and URM applicants for Gynecologic Oncology fellowship. During 2020 virtual Gynecologic Oncology fellowship interviews, we blinded one group of interviewers to written applications, including self-reported URM status. Interviewers visually interacted with the applicants but did not review their application. Interviewers submitted independent rank lists. We compared pooled rankings of blinded and non-blinded interviewers for all applicants and for URM applicants using appropriate bivariate statistics.We received 94 applications for two positions through the National Resident Matching Program, of which 18 (19%) self-identified as URM. We invited 40 applicants to interview and interviewed 30 applicants over six sessions. Ten interviewees (33%) self-identified as URM. Of 12 or 13 faculty interviewers during each interview session, 3 or 4 were blinded to the written application. There was no statistically significant difference in rank order when comparing blinded to non-blinded interviewers overall. However, blinded interviewers ranked URM applicants higher than non-blinded interviewers (p = 0.04). Blinding of written application metrics may allow for higher ranking of URM individuals.